Sustainable Development Strategies of China's Transportation Industry Under the Background of COVID-19 - Jun MA; Igor A. MAYBUROV (Communications of International Proceedings, 2020)
At the beginning of 2020, the "black swan" of COVID-19 began to wreak havoc in our country and globally, bringing a huge impact to people's lives. At present, the epidemic situation in my country has been clearly controlled, but its impact on economic growth has already appeared. As one of the industries most affected by the epidemic, the transportation industry will face huge challenges in the short term, but there is still room for sustainable development in the long term. Reduce or even completely eliminate the negative impact of COVID-19. This article analyzes and predicts the impact of COVID-19 on traffic from two aspects: road transportation and road construction and proposes countermeasures to ensure sustainable development. In order to ensure sustainable development, while seeking national policy support to resolve investment and financing difficulties, highway companies must take the initiative to turn the epidemic crisis into an opportunity for reform, reduce costs and increase efficiency, explore multiple channels of financing, and let the company pass the difficult period smoothly
Keywords: COVID-19; transportation; road construction; sustainable development; strategy.